Is Avian influenza virus still threatening humans? Preventative measures and treatment - Fordymacki, Jacek; Łagowski, Ryszard; Kosęda, Julia; Fetner, Barbara (Quality in Sport, 2025)
Introduction Global shift in the ecology of highly pathogenic avian influenza strains like H5N1 and the spread of avian influenza to mammals are raising concerns and prompting action in the event of a pandemic. Due to the nature of viruses, a future influenza pandemic is inevitable and preparedness for it vital. The aim of this article is to present the developed strategies for preventing pandemic influenza as a measure of preparedness for the upcoming threat. State of knowledge For public health purposes, influenza is divided into: seasonal, zoonotic and pandemic [1]. Although pandemic influenza spread very rare, it is of great concern due to its global reach and high mortality rate [2]. Health experts are concerned that a future pandemic could be caused by the H5N1 strain of the virus, an infection that can spread from birds to humans [3]. WHO, in collaboration with other institutions, continuously monitors influenza viruses. Based on risk assessment, it issues guidelines, develops surveillance strategies, and establishes a pandemic response plan. As part of preparedness for the next pandemic, specific influenza vaccines are developed and available antiviral drugs are being tested for their effectiveness against strains with pandemic potential. Summary Having appropriate policy and planning in place facilitates early response in order to suppress an influenza outbreak quickly, thus reducing the potentially catastrophic future impacts of a pandemic. Currently available antiviral medicines are mostly effective against the highly pathogenic strains of influenza A virus of concern. The Zoonotic influenza vaccines contains a strain matching the currently circulating clade to ensure protection. Effective plans will not succeed without the will to implement and execute them.